2012
DOI: 10.1111/j.1600-9657.2012.01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Push‐out bond strength of a nano‐modified mineral trioxide aggregate

Abstract: It is concluded that the force needed for the displacement of the nano-modification of WMTA (NWMTA) was significantly higher than for Angelus WMTA and Bioaggregate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
56
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 25 publications
15
56
1
2
Order By: Relevance
“…The failure modes of AMTA and GCMTA were predominately adhesive, but predominately cohesive for BD. These findings are in agreement with previous studies that reported adhesive bond failure with MTA and cohesive bond failure with BD 24,25) . The differences in bond strengths and failure modes among the tested cements may also be explained by the differences in the particle sizes, which may have an effect on the penetration of cement into dentinal tubules 25) .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The failure modes of AMTA and GCMTA were predominately adhesive, but predominately cohesive for BD. These findings are in agreement with previous studies that reported adhesive bond failure with MTA and cohesive bond failure with BD 24,25) . The differences in bond strengths and failure modes among the tested cements may also be explained by the differences in the particle sizes, which may have an effect on the penetration of cement into dentinal tubules 25) .…”
Section: Discussionsupporting
confidence: 83%
“…These findings are in agreement with previous studies that reported adhesive bond failure with MTA and cohesive bond failure with BD 24,25) . The differences in bond strengths and failure modes among the tested cements may also be explained by the differences in the particle sizes, which may have an effect on the penetration of cement into dentinal tubules 25) . Compared to the naturally derived MTA, the standardized components of BD as a manufactured material along with smaller particle size may be conducive to the formation of taglike structures and better micromechanical adhesion to dentine 4,23) .…”
Section: Discussionsupporting
confidence: 83%
“…Mineral trioxide aggregate (MTA), a calcium silicate-based cement, has rapidly gained popularity due to its ability to resist leakage and its superior marginal adaptation to the dentinal walls [1] . It is composed of tricalcium silicate, dicalcium silicate, bismuth oxide, tricalcium aluminate, and gypsum [6] . It has been used in numerous clinical situations such as direct pulp capping, repair of root perforations, apexogenesis, apexification, and as a root-end filling material [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 2 new calcium silicate-based cements were introduced into the market [6,10] . The first was Biodentine TM (Septodont, Saint Maur des Fossés, France), which is composed mainly of purified tricalcium silicate powder, small amounts of dicalcium silicate, calcium carbonate, and an opaque calcium chloride liquid [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Bu nedenle çalışmamızda dentine kimyasal olarak bağlanabilen bulk-fill kompozit rezinlerin, dentine kimyasal olarak bağlanamayan BA'dan daha yüksek bağlantı dayanımı gösterdiğini düşüncesindeyiz. Birçok çalışmada BA'nın MTA'dan daha düşük push-out bağlantı dayanımına sahip olduğu gösterilmiştir (8,19). Park ve ark.…”
Section: Discussionunclassified